(untitled) (Research, Society and Development, 2021)
Information and communication technology comprises a set of technological resources that enable the communication process. Among the available functions, the use of applications is cited, used in different areas, and covering different themes. In the context of mHealth, they participate in health promotion and education, characterized as an important tool for the population. The aim of this study was to identify, in national and international publications indexed in databases, the main methods adopted by researchers to validate applications in the health area. This is an integrative review study in which the following search was used: “Mobile Applications” AND “Health” AND “Validation Study”. Six studies were totaled, written in English, predominating, among them, the intention to examine the validity and reliability of the analyzed application (A3 and A5) and to validate the application (A4 and A6). The findings demonstrated a good application performance. The evaluation of mobile applications, through validation, guarantees more security to the technology, demonstrated by its effectiveness. Given the above, the need for a validation process with methodological rigor is highlighted, as well as publications on this topic aimed at the health field.